Adverse Selection or Moral Hazard, An Empirical Study1. (22nd March 2019) - Hui, Xiang; Saeedi, Maryam; Sundaresan, Neel
Abstract : Markets prone to asymmetric information employ reputation mechanisms to address adverse selection and moral hazard. In this paper, we use a change in such a reputation mechanism to examine its effect on improving adverse selection and moral hazard. In May, 2008, eBay changed its reputation mechanism to prevent sellers from giving negative feedback to buyers. This change was intended to prevent sellers from retaliating against buyers who gave them negative feedback. We observe an improvement in the overall quality of the marketplace as a result of this change. We attribute 49%–77% of this improvement to reduced adverse selection as low‐quality sellers exit the market or their market share drops, and the rest to a reduction in moral hazard as sellers improve the quality of their service.